Theoretical foundations of therapeutic and preventive measures from a position of functional system approach. Clinical experience. Demonstrative cases (Pain medicine, 2016)
Since olden times the attempts to present the research object – a living organism as a system (integrity) – have been marked in biology. The main sense of this conception is while studying the properties of the living organism as a system it is fundamentally and peremptorily unacceptable: a) to form the conception of them by additive method or to identify them with properties of structural formations that form it; b) to interpret (explain) on the assumption of knowledge and conceptions of properties that form its structural formations. The common theory of systems, theories of functional universal units, functional systems, and common adaptive syndrome are theoretically based on the methodology of complex of curative and preventive measures of activationadaptogenic therapy, the results of which are: a) the normalization of physiological and regenerative processes; b) the activation of reparative processes. The course of complex unspecific activationadaptogen therapy has been conducted in more than 450 patients. As a result of human organism transfer into the training condition of mild or increased activation the immunocompetent system more effectively performs its main biological function – preservation and recovery of genetically determined morphofunctional homeokinesis. The reflection of this is obtaining of positive clinical results: 1) the improvement of life quality; 2) the improvement of rates of organs and human organism system functions; 3) the recovery of genetically determined morphofunctional tissue organization in pathologically changed focuses (that is confirmed by ultrasound and Xray).
Keywords: system; organization; structural and functional; living organism; closed system; open system; condition; dynamic equilibrium; system behavior; equifinality; systemforming agent; functional system; homeokinesis; metabolism; morfofunctional homeokinesis; reaction; resistance; reactance; reliability; adaptation; compensatory unspecific; activationadaptogenic